Biogas Management: Advanced Utilization for Production of Renewable Energy and Added-value Chemicals - Yentekakis, Ioannis V.; Goula, Grammatiki (Frontiers in Environmental Science, 2017)
Biogas is widely available as a product of anaerobic digestion of urban, industrial, animal and agricultural wastes. Its indigenous local-base production offers the promise of a dispersed renewable energy source that can significantly contribute to regional economic growth. Biogas composition typically consists of 35-75% methane, 25-65% carbon dioxide, 1-5% hydrogen along with minor quantities of water vapor, ammonia, hydrogen sulfide and halides. Current utilization for heating and lighting is inefficient and polluting, and, in the case of poor quality biogas (CH4/CO2<1), exacerbated by detrimental venting to the atmosphere. Accordingly, innovative and efficient strategies for improving the management and utilization of biogas for the production of sustainable electrical power or high added-value chemicals are highly desirable. Utilization is the focus of the present review in which the scientific and technological basis underlying alternative routes to the efficient and eco-friendly exploitation of biogas are described and discussed. After concisely reviewing state-of-the-art purification and upgrading methods, in-depth consideration is given to the exploitation of biogas in the renewable energy, liquid fuels, transport and chemicals sectors along with an account of potential impediments to further progress.